THE IMPORTANCE OF UNDERSTANDING CULTURAL CONTEXT IN TRANSLATION BETWEEN ENGLISH AND UZBEK LANGUAGES - Ashurokhunova Dildora Toxir qizi, (TADQIQOTLAR.UZ, 2024)
Abstract: This article explores the importance of understanding cultural context in translation between English and Uzbek languages. It emphasizes the significance of considering linguistic and cultural differences, the impacts on communication, and the preservation of cultural authenticity during the translation process. By prioritizing cultural sensitivity and awareness, translators can ensure accurate and meaningful communication while fostering cross-cultural understanding and exchange.